Chronic Heroin Dependence Leading to Adrenal Insufficiency - Gautam Das (Case Reports in Endocrinology)
Opioids have been the mainstay for pain relief and palliation over a long period of time. They are commonly abused by drug addicts and such dependence usually imparts severe physiologic effects on multiple organ systems. The negative impact of opioids on the endocrine system is poorly understood and often underestimated. We describe a patient who developed severe suppression of the hypothalamic-pituitary adrenal (HPA) axis leading to secondary adrenal insufficiency due to long standing abuse of opioids.